2019
DOI: 10.1177/1759720x19831151
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of certolizumab pegol in rheumatoid arthritis patients in Canadian practice: 2-year results from the observational FαsT-CAN study

Abstract: Background: The aim of this study was to assess the real-world effectiveness and safety of certolizumab pegol (CZP) in rheumatoid arthritis (RA) patients, and the impact on patients’ productivity, pain, and fatigue, in Canadian practice. Methods: FαsT-CAN, a 2-year prospective, observational study, evaluated CZP use in Canadian adults with moderate to severe, active RA. The primary objective was to assess the proportion of patients achieving 28-joint Disease Activity Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The majority of patients achieved a EULAR response within 12 months (75.3%), which was sustained to 36 months among patients still in the study. Similar improvements in disease activity have been observed in previous observational studies into the long-term effec-tiveness of CZP (11)(12)(13). However, the EULAR response rate in ECLAIR was lower compared to the RAPID 1 study (96.2% at 12 months), which is likely due to higher baseline disease activity in the latter.…”
Section: Safetysupporting
confidence: 81%
See 1 more Smart Citation
“…The majority of patients achieved a EULAR response within 12 months (75.3%), which was sustained to 36 months among patients still in the study. Similar improvements in disease activity have been observed in previous observational studies into the long-term effec-tiveness of CZP (11)(12)(13). However, the EULAR response rate in ECLAIR was lower compared to the RAPID 1 study (96.2% at 12 months), which is likely due to higher baseline disease activity in the latter.…”
Section: Safetysupporting
confidence: 81%
“…Long-term observational data in more representative populations are therefore necessary, and are frequently considered or requested by health authorities. Several observational studies have previously reported on the effectiveness and safety of CZP in real-world settings in Canada, Germany and the UK, but an observational study of an anti-TNF has yet to be conducted in France (11)(12)(13). To this end, the French National Authority for Health requested an observational study to assess the effectiveness and safety of CZP up to 36 months in patients with moderate-to-severe RA in a real-world setting in France.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory tract infections. [ 178 , 179 ] Infliximab Pain relief and inhibition of cartilage destruction. Decrease in the expression of inflammatory cytokines in the synovial fluid and cartilage.…”
Section: Future Applications Of Mabs In Preclinical Development: Cancer Pain and Pain In Bone Fracturementioning
confidence: 99%
“…CANTORAL is the first study reporting the real‐world effectiveness and safety of a JAK inhibitor for moderate to severe RA in Canada and complements previous Canadian observational studies of patients with RA receiving bDMARDs (26–29). The proportion of patients with CDAI‐defined LDA and remission at month 6 was 52.9% and 15.4%, respectively, demonstrating the effectiveness of tofacitinib for moderate to severe RA.…”
Section: Discussionmentioning
confidence: 89%